Age and Body Size of the Turkish Smooth Newt Lissotriton schmidtleri (Raxworthy, 1988) (Urodela: Salamandridae) - Bülbül, Ufuk; Özkan, Hatice; Çalışkan, Dilay; Özkan Şeyma, Fatma (Institute of Biodiversity and Ecosystem Research at the Bulgarian Academy of Sciences, 2024)
Age and body size in a lowland population of Lissotriton schmidtleri in the İstanbul Province of Türkiye were examined by applying the skeletochronology method. The age range varies between 5 to 11 years in males and 4 to 8 years in females. The mean age and SVL values were 8.1 years and 36.28 mm in males and 6.4 years and 37.72 mm in females. The mean SVL and age values showed a significant difference between the sexes. The present study showed sexual dimorphism and different life expectancy between sexes. The estimated potential reproductive lifespan was higher in males than females.